Importance Of Implementing Visual Aids in Teaching Esp Students (Eurasian Journal of Learning and Academic Teaching, 2022)
This article informs about the importance of using visual aids in teaching ESP students. Moreover, it contains practical experiments on conducting lessons with and without visual aids to the biology students of Karakalpak higher education.